Additions to Larval Host Plants of Butterflies of the Western Ghats, Kerala, Southern India (Rhopalocera, Lepidoptera): Part 2 - Kalesh, S.; Prakash, Satya Krishna (Journal of the Bombay Natural History Society (JBNHS), 2015)
No Abstract.